MS-based glycomics: An analytical tool to assess nervous system diseases - Peng, Wenjing; Kobeissy, Firas; Mondello, Stefania; Barsa, Chloe; Mechref, Yehia (Frontiers in Neuroscience, 2022)
Neurological diseases have been affecting millions of people’s lives worldwide and keep increasing due to the aging population. Such diseases affect the nervous system and are characterized by a progressive decline in brain function and a progressive cognitive impairment, decreasing the quality of life for those having the disease and for their families and loved ones. The increased burden of nervous system diseases demands a deeper insight of the biomolecular mechanisms during disease development for the clinical diagnosis and drug design. Recently, more evidence has been related glycosylation to nervous system diseases. Glycosylation is a vital post-translational modification that mediates many biological functions, and aberrant glycosylation has been associated with a variety of diseases. Thus, the investigation of glycosylation in neurological diseases could provide novel biomarkers and information in disease pathology. During last decades, lots of techniques have been developed and utilized to facilitate the reliable and efficient glycomic analysis. Among them, mass spectrometry (MS) is considered as the most powerful tool in glycan analysis due to its high resolution, high sensitivity, and the ability to acquire adequate structural information for glycan identification. Along with MS, different approaches and strategies are employed to enhance the MS-based identification and quantitation of glycans in neurological samples. Here, we reviewed the advanced glycomic tools utilized in nervous system disease studies, including separation techniques prior to MS, fragmentation techniques in MS, and corresponding strategies. The glycan markers in common clinical nervous system diseases discovered by utilizing such MS-based glycomic tools are also summarized and discussed.